Integrating Tradition and Pedagogical Innovation: A Training of Trainers (ToT) Model for Sharaf Instruction in Ma'had Aly - Muhammad Fadhil Al Ghifari; Abdurrahman Abdurrahman; Luqman Hakim (AL-ISHLAH: Jurnal Pendidikan, 2026)
Arabic morphology (Sharaf) forms the foundation of Arabic literacy in Indonesian Islamic boarding schools (pesantren). However, limited pedagogical preparation among Sharaf teachers often leads to uneven learning outcomes and weak formative monitoring. This study develops a contextual Training of Trainers (ToT) model that integrates the classical text Amsilatu al-Taṣrīfiyyah, the traditional bandongan–sorogan instructional system, and active learning strategies within a structured formative assessment framework.A qualitative case study was conducted at Ma’had Aly An-Nur II Al-Murtadlo from July 2024 to June 2025. Data were collected through classroom observations, semi-structured interviews, and document analysis involving 16 teacher-trainees, 32 classes (≈1,255 students), and several institutional informants. The ToT program followed a four-stage cyclical model: short workshops, micro-teaching, peer observation and feedback, and journal-based reflection. Process indicators (teaching rubric scores and reflection quality) and outcome indicators (student Sharaf scores and hamzah-writing accuracy) were monitored quarterly. Data were analyzed using the Miles–Huberman–Saldaña framework.The findings show substantial improvements in pedagogical practice and student achievement. The average teaching rubric score increased from 2.8 to 3.6, while reflection quality rose from 2.5 to 3.7. Student learning outcomes also improved, with average Sharaf scores rising from 60–64 to 72–77 and hamzah-writing accuracy reaching 75–80%. These trends indicate a clear relationship between strengthened teacher pedagogical competence and improved student learning outcomes.The ToT–Sharaf model demonstrates that pesantren traditions can function as catalysts for pedagogical innovation when combined with active learning and formative assessment. The model offers a replicable framework for teacher development and sustainable improvement of Arabic morphology instruction in pesantren contexts.